SOX7 blocks vasculogenic mimicry in oral squamous cell carcinoma. (29th March 2021) - Hong, Kyoung‐Ok; Oh, Kyu‐Young; Yoon, Hye‐Jung; Swarup, Neeti; Jung, Minjung; Shin, Ji‐Ae; Kim, Jung‐Hwan; Chawla, Kunal; Lee, Jae‐Il; Cho, Sung‐Dae; Hong, Seong‐Doo
Abstract: Background: Vasculogenic mimicry (VM) is the formation of an alternative circulatory system by aggressive tumor cells. The characteristics of VM and its underlying mechanism in oral squamous cell carcinoma (OSCC) remain unclear. This study aims to determine the relationship between VM in OSCC tissues and clinical outcomes and to investigate the biological role of SOX7 in VM in OSCC cells. Methods: CD31/PAS staining was performed to evaluate VM in OSCC tissue. The relationships between VM and clinicopathological variables, and VM and SOX7 levels were analyzed. The correlation between SOX7 levels and cancer cohorts was investigated using in silico analysis. VM formation assay was performed to observe VM in vitro. To investigate the role of SOX7 in VM formation, SOX7 was transiently over‐expressed in SCC‐9 cells. VM‐modulating genes were identified by Western blotting. Results: We found a positive correlation between VM and lymph node metastasis and patient survival in OSCC ( p = 0.003). In silico analysis from The Cancer Genome Atlas and Gene Expression Omnibus database showed that down‐regulation of SOX7 expression was significantly correlated with OSCC patients ( p = 0.0187) and lymph node metastasis ( p = 0.0017). We also found that the presence of VM in OSCC tissue was inversely associated with SOX7 expression ( p = 0.020). We observed that overexpression of SOX7 impaired VM formation by reducing the expression of VE‐cadherin, thereby inhibiting cell migration and invasion. Conclusion: These results suggest that SOX7 plays an important role in the regulation of VM formation and may inhibit OSCC metastasis.